Characterization of the complete chloroplast genome of Boschniakia himalaica J. D. Hooker & Thomson (Orobanchaceae), a medicinal species in southwest China - Zhou, Nong (Mitochondrial DNA. Part B. Resources, 2019)
Boschniakia himalaica is a medicinal plant in southwest China. In this study, we sequenced complete chloroplast (cp) genome of B. himalaica to investigate its phylogenetic relationship in Orobanchaceae. The chloroplast genome was 106,466 bp in length with 37.3% overall GC content, including a large single copy (LSC) region of 49,606 bp, a small single copy (SSC) region of 5572 bp, and a pair of inverted repeats (IRs) of 25,644 bp. The cp genome contained 84 genes, including 50 protein-coding genes, 30 tRNA genes, and 4 rRNA genes. The phylogenetic analysis indicated B. himalaica was closely related to Cistanche deserticola.